Priority setting and health policy and systems research - Bennett Sara C; Ranson Michael K (BMC, 2009)
Abstract Health policy and systems research (HPSR) has been identified as critical to scaling-up interventions to achieve the millennium development goals, but research priority setting exercises often do not address HPSR well. This paper aims to (i) assess current priority setting methods and the extent to which they adequately include HPSR and (ii) draw lessons regarding how HPSR priority setting can be enhanced to promote relevant HPSR, and to strengthen developing country leadership of research agendas. Priority setting processes can be distinguished by the level at which they occur, their degree of comprehensiveness in terms of the topic addressed, the balance between technical versus interpretive approaches and the stakeholders involved. When HPSR is considered through technical, disease-driven priority setting processes it is systematically under-valued. More successful approaches for considering HPSR are typically nationally-driven, interpretive and engage a range of stakeholders. There is still a need however for better defined approaches to enable research funders to determine the relative weight to assign to disease specific research versus HPSR and other forms of cross-cutting health research. While country-level research priority setting is key, there is likely to be a continued need for the identification of global research priorities for HPSR. The paper argues that such global priorities can and should be driven by country level priorities.